Effect of Sr on the microstructure and biodegradable behavior of Mg–Zn–Ca-Mn alloys for implant application. (5th September 2018) - Wang, Jingfeng; Ma, Yao; Guo, Shengfeng; Jiang, Weiyan; Liu, Qingshan
Abstract: In this paper, the effect of Sr on the microstructure and bio-corrosion behavior of Mg65.2−x Zn30 Ca4 Mn0.8 Srx (x = 0, 0.3, 0.5 and 0.8) amorphous matrix composite were investigated by X-ray diffraction, differential scanning calorimetry, scanning electron microscope, electrochemical measurements, immersion test and in vitro cytotoxicity test, respectively. Compared to the Mg–Zn–Ca-Mn alloy, the Sr-bearing alloys with minor Sr incorporation improved the glass formation ability and bio-corrosion resistance significantly. The corrosion products of the Mg65.2−x Zn30 Ca4 Mn0.8 Srx (x = 0, 0.3, 0.5 and 0.8) alloys mainly contained Zn(OH)2, hydroxyapatite and phosphate after 124 h static immersion test, which were beneficial to the bone growth. The results suggested that the novel Mg64.7 Zn30 Ca4 Mn0.8 Sr0.5 alloy possessed a good corrosion resistance and biocompatibility, showing a promising candidate for the biodegradable implants. Graphical abstract: Unlabelled Image Highlights: The Mg65.2-x Zn30 Ca4 Mn0.8 Srx (x=0, 0.3, 0.5 and 0.8) amorphous matrix composites were prepared by copper mold casting Introducing 0.3at% and 0.5at.% of Sr to Mg66 Zn30 Ca4 Mn0.8 would improve glass forming ability and corrosion property. The cellular-behavior evaluation demonstrated that Mg64.7 Zn30 Ca4 Mn0.8 Sr0.5 alloy showed good vitro cytocompatibility. A schematic diagram was proposed to illustrate the corrosion mechanism.